Development of mathematical model to study the effect of indoor air quality parameters and optimization using response surface methodology. (2021) - Prakash, K.B.; Subramaniayan, C.; Chandrasekaran, M.; Manoj Kumar, P.; Saravanakumar, S.
Abstract: This paper explores opportunities to know about the optimal setting and influencing parameters of Indoor Air Quality characteristics (IAQ) of the air-conditioned car by response surface methodology (RSM). The trials were designed by the design of experiments and performed to cram the result of input parameters i.e human load, fresh air supply, and air velocity, on the Indoor Air Quality parameters i.e Temperature, Relative humidity, Oxygen and carbon dioxide inside the car air-conditioned space. This work traveled around on finding the mathematical model to show a relationship and interactions of IAQ parameters. Also, this work focused on finding the optimum setting controlling parameters by RSM. It recommend that car AC setting position of fresh air supply knob, and Air velocity (blower speed knob) for different human loads. This study be evidence for that the Response Surface methodology (RSM) techniques were suitable for optimizing the IAQ parameters with the minimum number of trials.